The role of talent management strategies and the characteristics of knowledge makers in enhancing organizational citizenship behavior - an exploratory study of the opinions of a sample of employees of the Student Registration Division and their managers i - Ahmed Abed Allah A'mana (Iraqi Journal for Administrative Sciences, 2025)
This research sought to determine the role of talent management strategies and the characteristics of knowledge makers in enhancing organizational citizenship behavior by applying it in our Iraqi organizations. In order to achieve this, the dimensions (strategies) of talent management were adopted (attracting talent, selecting talent, developing talent, maintaining talent), and the dimensions (strategies) of talent management were adopted. Knowledge creators (achievements and challenges, individual growth, excellence, independence, directed goals). Also, the dimensions of organizational citizenship behavior were adopted (altruism, civility, awareness of conscience, sportsmanship, civilized behavior), and the employees of the registration divisions and their managers in the colleges of the University of Karbala were chosen as a field for research through a questionnaire form. It included (100) employees in the investigated colleges, in addition to personal interviews. The Spearman correlation coefficient and the t-test were used to determine the significance of the relationship between the variables, and the F-test was used to determine the significance of the regression equation. R-test was also used to interpret the amount of the effect of the variable. The independent variable in the dependent variable. One of the most important conclusions reached is that talent management strategies and the characteristics of knowledge makers have an effective role in enhancing organizational citizenship behavior. The research concluded with a number of recommendations, including the following: Focus on attracting talented workers, which enables the college to enhance citizenship behavior. Focus on attracting knowledge makers. Benefiting from their stock of knowledge acquired as a result of experience and learning and investing it in enhancing organizational citizenship behavior, working to encourage the practice of citizenship behaviors necessary to reward their spontaneous and voluntary efforts. Consolidating and supporting positive organizational values in the work environment, such as justice, equality, participation, and loyalty to the organization, the necessity of moving from the local concept of citizenship to global and humanitarian citizenship, especially in our globally open and culturally diverse society.